California Elected Women's Association for Education and Research Bylaws
This document contains the bylaws of the California Elected Women's Association for Education and Research, outlining its name, purposes, structure, and governance. The Association's purposes include promoting women's participation in public affairs, encouraging women to seek elective office, fostering research and education on public issues affecting women, and serving as an informational clearinghouse, while explicitly prohibiting endorsements. The bylaws detail membership categories, officer roles, executive committee responsibilities, meetings, elections, parliamentary authority, and amendment procedures, establishing a formal organizational framework.